ASSESSING THE EFFECTIVENESS OF PHYSICAL EDUCATION CURRICULUM IMPLEMENTATION IN PROMOTING PHYSICAL FITNESS IN SCHOOLS - Junaid Hamid Bhat; Dr Vijay Kumar (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The importance of physical education (PE) in fostering holistic development among students is widely recognized; however, the degree to which PE curricula are effectively implemented remains a critical concern in many educational systems. This study assesses the effectiveness of physical education curriculum implementation in promoting physical fitness in schools. Using a mixed-method approach, the research analyzes the relationship between curriculum design, teacher preparedness, instructional methods, and student fitness outcomes. Data were collected from 200 students and 25 PE teachers across government and private schools. The findings reveal that effective curriculum implementation characterized by structured lesson plans, adequate facilities, and trained teachers positively correlates with improved physical fitness levels among students. The study concludes that periodic curriculum evaluation, professional development for PE teachers, and enhanced infrastructure are essential for maximizing the benefits of physical education in school environments.